Job retention among healthcare workers in Tabora province, Tanzania - Mfaume, Rashid S.; Kamba, Gunini P.; Morikawa, Masahiro J. (International Journal Of Community Medicine And Public Health, 2017)
Background: Manpower shortage is a serious problem in healthcare in sub-Saharan Africa. We tried to characterize the health manpower retention and attrition pattern in Tabora province, Tanzania comparing the types of health facilities and different job levels through a review of provincial health manpower registration ledger retrospectively for 3 years, from 2012-2015. Methods: The job retention audit was planned through provincial human resources registration in 6 districts within the Tabora province and at the Kietete provincial referral hospital. The audit was conducted from August and September 2015 by notifying by email to obtain job retention from the human resource registration ledger for 3 years from 2012 to 2015. We compared retention patterns among different types of facilities and among different levels of healthcare personnel. Results: The overall job attrition rate for 3 years in Tabora was 5.7%. Among different level of healthcare facilities, compared with hospitals, lower-tier facilities (dispensaries) had a better job retention but the was not statistically significant. Among job levels, highest job level, medial officers had significantly higher rate of attrition compared with nurses. Lower-level job category (clinical officers) seems to have better retention rate but again it was not statistically significant. Conclusions: Our study will incur the need for bigger and longer follow-up study to examine the trend we observed here; lower-tier facilities (dispensaries) and lower-level levels (clinical officers) seem to have better job retention. The further study is expected to contribute how we allocate our budget and human resources in the provincial healthcare structure in the future.